A struggle to change the world: Pelin Esmer’s documentary the play - Kırel, Serpil (My University, 2010)
This article is about the important position that women’s experiences occupy in feminist filmmaking, about women’s images in the context of film production in Turkey, and about the function of various narrative styles in documentary films. Pelin Esmer’s documentary The Play (Oyun, 2005) offers the opportunity to reconsider the importance of sharing intercultural works about women within the paradigm of a national and global audience (Kırel, 2009).
Keywords: film; feminism; documentary; stereotypes; counter-gaze